The Psychological Immune Competence Inventory: A Pilot Validation Study in Slovakia - Široká, Kristína; Antalová, Annamária; Čechová, Daniela (European Journal of Mental Health, 2024)
Introduction: Psychological immunity refers to an individual’s potential to cope with psychological risk factors, as well as to promote and maintain mental health and well-being. The method of its measurement is the Psychological Immune Competence Inventory (PICI), which appears to have good psychometric parameters. Despite the use of translated versions in various foreign studies, the authors have found no studies verifying its factor structure or reliability. Aims: In this article, our objective is to present the results of the PICI pilot validation in Slovakia. The Slovak version of PICI was expected to have psychometric properties comparable to those of the original version. Methods: We collected data from a research sample of 213 healthcare students (162 women and 51 men) aged 19 to 35 years (M = 21.18; SD = 2.81), and validated the internal structure of the inventory using Structural Equation Modeling (SEM) via employing the DWLS estimation method. The convergent validity of individual factors was further verified by correlation with personality traits, psychopathological symptoms, preferred coping strategies and trait emotional intelligence. Results: The results of the second-order confirmatory analysis indicate an acceptable fit of the original model to our data. The convergent validity of the observed individual psychological immunity factors was also supported. Conclusions: The Slovak version of PICI showed promising psychometric properties. The research serves as a reference to Slovak standardization. Nevertheless, further validation is recommended in a representative sample.